2000
DOI: 10.1128/mcb.20.13.4806-4813.2000
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Amino Acid Residues in theCaenorhabditis elegansPOU Protein UNC-86 That Mediate UNC-86–MEC-3–DNA Ternary Complex Formation

Abstract: The POU homeodomain protein UNC-86 and the LIM homeodomain protein MEC-3 are essential for the differentiation of the six mechanoreceptor neurons in the nematode Caenorhabditis elegans. Previous studies have indicated that UNC-86 and MEC-3 bind cooperatively to at least three sites in the mec-3 promoter and synergistically activate transcription. However, the molecular details of the interactions of UNC-86 with MEC-3 and DNA have not been investigated so far. Here we used a yeast system to identify the functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Earlier studies have shown the cooperative role of the MEC-3 and UNC-86 transcription factors in defining the terminal fate of the TRNs and in maintaining the expression of MEC-3 (13)(14)(15)(16)(17)(18)). Here we demonstrate that, due to stochastic fluctuations, MEC-3 autoregulation is insufficient to maintain TRN differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have shown the cooperative role of the MEC-3 and UNC-86 transcription factors in defining the terminal fate of the TRNs and in maintaining the expression of MEC-3 (13)(14)(15)(16)(17)(18)). Here we demonstrate that, due to stochastic fluctuations, MEC-3 autoregulation is insufficient to maintain TRN differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…UNC-86 is needed not only to produce touch cell lineages but also to initiate transcription from the mec-3 gene (12). The maintained expression of mec-3 and the subsequent expression of TRN characteristics require the combinatorial action of MEC-3 and UNC-86; MEC-3 acts (as a coactivator with UNC-86) in an autoregulatory loop to maintain its own expression and to induce the expression of TRN-specific genes (13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…unc-86 is expressed throughout the touch cell life, suggesting that it may function in maintenance as well as in lineage specification (27,122,191). MEC-3 and UNC-86 associate to form heterodimers that bind to well-defined sites in the mec-3 and other touch cell-specific gene promoters (such as mec-4 and mec-7) to stimulate gene expression (252,344,345,447,449,474,475). The MEC-3 LIM homeodomain and the UNC-86 POU homeodomain are sufficient to mediate interaction in vitro, but more of each protein is needed for heterodimer formation on DNA in vivo (474,475).…”
Section: Genetics and Molecular Biology Of The Gentle Body Touch Respmentioning
confidence: 99%
“…In C. elegans touch receptor neurons, the LIM-HD factor, MEC-3 and the POU protein UNC-86, physically interact to control specification (Rockelein et al, 2000;Xue et al, 1993). In the pituitary, the LIM domain of Lhx3 (P-Lim) specifically interacts with the Pit1 POU domain and is required for synergistic interactions with Pit1 (Bach et al, 1995).…”
Section: Development 131 (21)mentioning
confidence: 99%
“…Furthermore, LIM-HD and POU members have been shown to function together to direct cell differentiation in both vertebrates and invertebrates. For example, UNC-86 and the LIM-HD factor MEC-3 interact genetically and physically to regulate tough sensory neuron differentiation in C. elegans (Rockelein et al, 2000;Xue et al, 1993).…”
Section: Introductionmentioning
confidence: 99%